Proceeding of the international symposium on the theatre in the east and the west (Japanese National Commission, 1965)
This book contains important papers on the strangeness production processes and strangeness nuclear physics resulting from electromagnetic interaction. Both experimentalists and theorists in the field present information on recent activities and discuss the prospects of related fields.